Characterization of Mechanical Allodynia and Skin Innervation in a Mouse Model of Type-2 Diabetes Induced by Cafeteria-Style Diet and Low-Doses of Streptozotocin - Castañeda-Corral, Gabriela; Velázquez-Salazar, Norma B.; Martínez-Martínez, Arisai; Taboada-Serrano, Juanita N.; Núñez-Aragón, Pablo N.; González-Palomares, Laura; Acosta-González, Rosa Issel; Petricevich, Vera L.; Acevedo-Fernández, Juan José; Montes, Sergio; Jiménez-Andrade, Juan Miguel (Frontiers in Pharmacology, 2021)
Background: Painful distal symmetrical polyneuropathy (DPN) is a frequent complication of type-2 diabetes mellitus (T2DM) that commonly presents as neuropathic pain and loss of skin nerve fibers. However, there are limited therapies to effectively treat DPN and many of the current animal models of T2DM-induced DPN do not appear to mirror the human disease. Thus, we validated a DPN mouse model induced by a cafeteria-style diet plus low-doses of streptozotocin (STZ). Methods: Female C57BL/6J mice were fed either standard (STD) diet or obesogenic cafeteria (CAF) diet for 32 weeks, starting at 8 weeks old. Eight weeks after starting diets, CAF or STD mice received either four low-doses of STZ or vehicle. Changes in body weight, blood glucose and insulin levels, as well as oral glucose- and insulin-tolerance tests (OGTT and ITT) were determined. The development of mechanical hypersensitivity of the hindpaws was determined using von Frey filaments. Moreover, the effect of the most common neuropathic pain drugs was evaluated on T2DM-induced mechanical allodynia. Finally, the density of PGP 9.5+ (a pan-neuronal marker) axons in the epidermis from the hindpaw glabrous skin was quantified. Results: At 22-24 weeks after STZ injections, CAF+STZ mice had significantly higher glucose and insulin levels compared to CAF+VEH, STD+STZ, and STD+VEH mice, and developed glucose tolerance and insulin resistance. Skin mechanical sensitivity was detected as early as 12 weeks post-STZ injections and it was significantly attenuated by intraperitoneal acute treatment with amitriptyline, gabapentin, tramadol, duloxetine, or carbamazepine but not by diclofenac. The density of PGP-9.5+ nerve fibers was reduced in CAF+STZ mice compared to other groups. Conclusions: This reverse translational study provides a painful DPN mouse model which may help in developing a better understanding of the factors that generate and maintain neuropathic pain and denervation of skin under T2DM and to identify mechanism-based new treatments.